2023
DOI: 10.1002/jbmr.4828
|View full text |Cite
|
Sign up to set email alerts
|

Relative Effects of Radiation‐Induced Changes in Bone Mass, Structure, and Tissue Material on Vertebral Strength in a Rat Model

Abstract: The observed increased risk of fracture after cancer radiation therapy is presumably due to a radiation‐induced reduction in whole‐bone strength. However, the mechanisms for impaired strength remain unclear, as the increased fracture risk is not fully explained by changes in bone mass. To provide insight, a small animal model was used to determine how much of this whole‐bone weakening effect for the spine is attributable to changes in bone mass, structure, and material properties of the bone tissue and their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Long-term follow-up examinations revealed that pediatric oncology patients treated with RT suffer from major growth disturbances. This includes the asymmetry of chest and ribs, scoliosis, kyphosis, pain at the radiation site, leg-length inequality, and in some cases the development of secondary tumors [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term follow-up examinations revealed that pediatric oncology patients treated with RT suffer from major growth disturbances. This includes the asymmetry of chest and ribs, scoliosis, kyphosis, pain at the radiation site, leg-length inequality, and in some cases the development of secondary tumors [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%